Evaluation of the Effect of Operating Parameters on the Performance of Orifice/Porous Pipe Type Micro-bubble Generator - Benny Arif Pambudiarto; Aswati Mindaryani; D. Deendarlianto; Wiratni Budhijanto (Journal of Engineering and Technological Sciences, 2020)
The micro-bubble generator (MBG) is a novel aeration technology utilizing the concept of fluid flow through an orifice, where air is sucked into the internal chamber of the MBG by the pressure difference created by the orifice and immediately pushed by the high-velocity flow of the fluid. This mechanism creates micro-size bubbles with a high dissolution rate. This study focused on studying the effect on the oxygen dissolution rate of the two most important operating parameters, i.e. the volumetric flow rate of the liquid (QL) and the volumetric flow rate of the air (QG). Various combinations of values for QL and QG were systematically compared by means of the oxygen mass transfer coefficient (kLa). The experiment was carried out in a transparent container of 2.8 m x 0.6 m x 0.4 m filled with tap water that was aerated using an orifice/porous-pipe type MBG. The dissolved oxygen (DO) values were measured at distances of 60 cm, 120 cm, and 180 cm from the MBG outlet. The experiment was designed with five different values for QL and QG respectively. The results showed that the value of kLa, which is proportional to the oxygen dissolution rate, increased asymptotically with increasing QL value, while the QG values did not significantly affect the kLa value.